(untitled) (Experimental biology, 2024)
The article was written as part of the Ministry of Science and Higher Education of the Republic of Kazakhstan’s project AP 23486220, titled “Study of the important organ systems reactivity in the main commercial fish species of the Ile-Balkhash basin under anthropogenic load.” (2024-2026). The article represents the study investigating the long-term effects of polyethylene terephthalate (PET) microplastics on zebrafish (Danio rerio). Zebrafish exposed to PET microplastics at concentrations of 1.9 mg/l and 5.64 mg/l exhibited significant kidney and gill damage. This included necrosis, circulatory disorders, and tissue damage. Histological analysis revealed specific pathological changes such as vacuolization and hyaline-droplet degeneration in kidneys, and destruction of epithelium and lamellae in gills. Notably, no compensatory-adaptive reactions in gills were observed, indicating a lack of adaptation to prolonged exposure. These findings suggest that microplastics may migrate through the bloodstream, disrupting normal kidney and gill structures. The study highlights the severe impact of microplastic pollution on fish organs, emphasizing the urgent need for further research to develop strategies for mitigating microplastic pollution in aquatic ecosystems. Additionally, the observed lack of adaptive responses underscores the potential for significant ecological consequences, urging immediate attention to address this critical environmental issue.